Joseph Conrad : a psychoanalytic biography - Meyer, Bernard C. (Bernard Constant), 1910-1988 (Princeton legacy library., 1967)
Joseph Conrad once voiced the hope that from the reading of his pages might "emerge at last the vision of a personality: the man behind the books ... a coherent justifiable personality both in its origin and its actions." Dr. Meyer arrives at a unified picture of Conrad's personality by applying psychoanalytic principles and insights to two main sets of data on Conrad: his unusual history and his creative work. Basic psychological and emotional patterns appear repetitively, and Dr. Meyer concludes that Conrad's art served an important psychological function in his life-the achievement through his creative fiction of a corrective revision of painful reality. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905